Synthesis of dilactone bridged terphenyls with crankshaft architectures. Issue 2 (14th January 2015) - Dressler, Justin J.; Miller, Sarah A.; Meeuwsen, Brian T.; Riel, Asia Marie S.; Dahl, Bart J.
Abstract: Three highly fluorescent dilactone bridged terphenyls with crankshaft architectures have been synthesized. This general class of compounds is relatively unexplored. These compounds have been characterized by fluorescence and UV–vis spectroscopy. For all three compounds, a direct correlation between the rigidity of the terphenyl system and the strength of absorption and emission of light has been observed. Preliminary studies have indicated that compounds with this architecture have the potential to be useful as pH-driven molecular switches and/or sensors with instant fluorescence attenuation at high pH values. Graphical abstract: